Jurnal Kata: the dehumanizing American dream in DAVID MAMET's Glengarry glen ross - Mehdi sepehrmanesh, Ehsan dehghani (Prodi Bahasa Inggris Fak sastra PETRA, 2014)
the American dream is recurrent theme in American Literature